CONSUMER BEHAVIOR ANALYSIS OF ANTAM PEGADAAN'S GOLD PURCHASE DECISIONS IN THE DIGITAL ERA - Nora Anisa Br Sinulingga; Risa Kartika Lubis; Windy Nadia; Jeli Purama Sari Buulolo (Jurnal Multidisiplin Sahombu, 2022)
In the current era of digitalization, it is important for every company to conduct a Consumer Behavior Analysis of Antam Pegadian's Gold Purchase Decision in the Digital Age whose goal is to develop wings in achieving company profitability. This researcher aims to determine consumer behavior towards Antam Pegadian's Gold Purchase Decision in the Digital Age. The type of research used is descriptive qualitative. The data that is processed is the result of interviews and key informants at the pawnshop. Data collection techniques used are Observation, Interview, and Documentation. While the data analysis technique used in this research is data collection either through observation or interviews, data reduction, data presentation and conclusions. Based on the results of research conducted by researchers, the conclusion that can be drawn is that all characteristics of consumer behavior affect Antam Pegadian's purchase decision of Gold in the Digital Era.